2022
DOI: 10.3390/app12031534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Directionality on the Seismic Response of Typical RC Buildings

Abstract: Current seismic analysis contemplates the simultaneous use of the orthogonal components of an earthquake in order to determine the structural stresses closer to reality. This has led to these components being combined considering a fraction of them, as applying them completely would lead to excessively conservative results. However, their application is carried out considering that the direction of the components coincides with the orientation of the orthogonal axes that define the resistant structure. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Reinforced concrete structures are present in nearly all populated areas with a variety of structural typology and purpose, from individual houses to condominiums, schools, hospitals, a.s.o. Such diverse typology means different behaviour during a seismic event, a behaviour that should be correctly assessed and understood [1,4]. Reinforced concrete frame structures provide both the required ductility and the strength necessary to resist lateral loads such as those induced by earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete structures are present in nearly all populated areas with a variety of structural typology and purpose, from individual houses to condominiums, schools, hospitals, a.s.o. Such diverse typology means different behaviour during a seismic event, a behaviour that should be correctly assessed and understood [1,4]. Reinforced concrete frame structures provide both the required ductility and the strength necessary to resist lateral loads such as those induced by earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various research works have noticed the effect of the excitation direction on the resulting response, mainly with an inflexible base assumption as in Ning et al [25], Bugueño et al [26], Athanatopoulou [27] and Altunişik and Kalkan [28]; and also considering the influence of a flexible base, as in the research by Askouni and Karabalis [29,30] and Katsimpini et al [31]. In later works [25][26][27][28][29][30][31], efforts have been carried out to identify the crucial direction of the excitation judging from the most unfavorable response characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The ground excitation considered is of the sequential type, although this study does not attempt to solely focus on the effects of multiple ground excitations compared to single events, which is already investigated in the literature, e.g., [18][19][20][21][22]. In addition, the effect of the earthquake direction is explored in the current elastoplastic dynamic analyses, as this has been shown to possibly affect the seismic structural behavior in various research works, including [7,[25][26][27][28][29][30][31]. The consideration of the elastoplastic performance of reinforced concrete or steel structural members is simply incorporated in the analysis model, without interfering with more detailed mechanical models available in the literature on the respective mechanical characteristics of r/c and steel cross-sections, which do not belong to the current study's focus.…”
Section: Introductionmentioning
confidence: 99%
“…Athanatopoulou formulated equations for calculating the critical ASI from the time-history response of a linear elastic structure subjected to unidirectional excitation (Athanatopoulou, 2005). The influence of the ASI on the nonlinear responses of symmetric and asymmetric building structures has been studied by several researchers (e.g., Rigato and Medina, 2007;Fontara et al, 2012;Kostinakis et al, 2013;Magliulo et al, 2014;Reyes and Kalkan, 2015;Kalkan and Reyes, 2015;Faggella et al, 2018;Bugueño et al, 2022). Most of these studies have shown that the critical ASI depends not only on the response quantities of interest and the shape of the elastic response spectrum of the ground motions but also on the intensity of the ground motions.…”
Section: Introductionmentioning
confidence: 99%